Perceptions of Masalembu Island Communites on Importance and Threat Values of Small Island Resources - Ihsannudin Ihsannudin; Sukmo Pinuji; Rif’ah Inayati; Subejo Subejo; Suadi Suadi (Universitas Andalas, 2021)
Small islands have the nature of remoteness and vulnerability and commonly occupied by multi-ethnic communities that cause differences in the way they perceive natural resources. This study aimed to find out the communities perceptions on the importance and threat values of resources. This study was conducted through a survey method in Masalembu island, Sumenep Regency, East Java, Indonesia. The data were analyzed using descriptive frequency analysis method. The study shows the resources perceived very important are the sea, mosques and 4 resources with the same score (schools, madrasah, public health centers, and markets). Meanwhile, the top 3 resources that highly threatened are the sea, breakwater, and sand mining. There exists a paradox for marine resources because they are perceived very important and contrastively very threatened at the same time. Comprehensive regulations, programs, and policies are needed in the development related to the sea. In this case, social development, education, health, and economic cannot be ignored. Rehabilitation of mangrove vegetation should be encouraged in ex-mining and abrasion areas, taking roles asbreakwateras well as a means to increase the wealth of marine and coastal resources.